De Sint-Annakerk in Aldeneik: Historische overleveringen en archeologische feiten - Neskens, Anja (Publications de la Société Historique et Archéologique dans le Limbourg, 2024)
The Maasland embraces the beautiful valley of the river Meuse. It is in this region that Aldeneik is situated on the left side of the river Meuse, just on the border with the Dutch province of Limburg. Aldeneik or as they say ‘Oude Eycke’ is founded before the current city of Maaseik of ‘Nieuwe Eycke’.Historical sources assign the origin of Aldeneik to the construction of a Christian church for the two holy sisters Harlindis and Relindis in the early eighth century. The confrontation of historical sources with archaeological research in 2008 offers a new insight into the construction history of the current Saint Anna’s church in Aldeneik. The most striking novelties are the lack of finds related to the wooden Merovingian church. Nevertheless, the research done on the relics in 2016 raises the possibility of starting the Merovingian phase as early as the 7th century. The greatest attention is devoted to the evidence that the Romanesque church can be dated earlier, back to the 11th century instead of the earlier proposed 12th century. It goes even further. Archaeological research showed that the Romanesque church was still in use after the completion of the Gothic renovations.